Isolation, Identification, and Quantification of Two Compounds from Cassia glauca Cultivated in Iraq - Kanaan M Abdlkareem, Shamam; kadhim, Enas Jawad Kadhim (Iraqi Journal of Pharmaceutical Sciences, 2023)
The Cassia glauca Lam. is the tree that belongs to the Fabaceae family and is native to India has many uses in indigenous systems of medicine, folk medicine, and traditional Brazilian medicine. Has many pharmacological activities such as anti-diabetic, antibacterial, antifungal, antioxidant, anti-hemolytic, anticancer, cardio-protective, and Hepato-protection. The aim of study is to Isolation, identification, and quantification of some compounds from aerial parts of Cassia glauca since no phytochemical investigation had previously been done in Iraq for this plant. The aerial parts were defatted in n. hexane for 48 hours. The defatted materials were extracted in 85% ethanol using the hot method (soxhlet), then the extract was fractionated using different solvents (chloroform, ethyl acetate, and n-butanol). High-performance liquid chromatography (HPLC), was used for identification and quantification by using authenticated standards, and preparative layer chromatography (PLC) was used for the isolation of the identified compounds. The isolated compounds were identified after isolation by liquid chromatography Mass Spectrometry LC-MS/MS-Q-TOF method. The different chromatographic and spectroscopic methods results indicate the presence of luteolin and chlorogenic acid in the ethyl acetate fraction and n-butanol fraction respectively and estimated the quantity as (130.77µg/1g) for luteolin, and (0.0006%) for chlorogenic acid from 50g of plant material.